The Paradigm of Economic Justice from Abu 'Ubaid's Perspective and Its Relevance in Indonesia - Irsad; Purwati, Poni; wartoyo, Wartoyo (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study examines the relevance of Abu Ubaid's Islamic economic thought, particularly aspresented in his seminal work, Kitab al-Amwal, to the concept of economic justice in theIndonesian context. The research aims to examine how his principles—rooted in justice, public finance, zakat distribution, and state responsibility—can be applied to modern economic governance in a Muslim-majority country. Using a qualitative approach with a library research method, the study analyzes primary and secondary literature, including classical texts and contemporary journal articles from scholarly databases such as Scopus and ProQuest. The findings highlight four key ideas in Abu Ubaid’s philosophy: justice as the core principle of economic order, wealth distribution based on need, state-managed public finance for societal welfare, and balanced taxation respecting all citizens' rights and obligations. These principles align with Indonesia’s constitutional goals, especially Article 33 of the 1945 Constitution, which emphasizes equitable efficiency and economic democracy. However, the study notes that current zakat administration and fiscal practices in Indonesia have not fully realized Abu Ubaid’s ideals. The research contributes theoretically to Islamic economics by contextualizing classical thought in a modern nation-state and offers practical implications for policymakers. It underscores the need to integrate classical Islamic values—such as just taxation and state accountability—into Indonesia’s fiscal strategy to promote social justice, reduce poverty, and support sustainable development.